DEVELOPING GRAMMAR AND VOCABULARY TEXTBOOK FOR ENGLISH EDUCATION STUDENTS AT THE HINDU STATE UNIVERSITY IGB SUGRIWA DENPASAR - Komang, Trisna Dewi; Made Wahyu Mahendra; Kadek Dwi Sentana (LUNAR, 2025)
This research was a development research (R&D) which aimed to develop a textbook entitled “Grammar and vocabulary” for English for Tourism course in the English Education Department at the Hindu State University I Gusti Bagus Sugriwa Denpasar. Data were obtained through observation, questionnaires and documentation techniques. Data were analyzed qualitatively and quantitatively. The results of this study indicated that the results of the CVI calculation for 2 material experts were 0.99 (1) and the CVI calculation for product design is 0.97 so that it is quite close to the Lawshe minimum limit value. Thus the material contained in the book " Grammar and vocabulary " was declared valid and feasible to be used. The output of this research was a book entitled " Grammar and vocabulary ".